2015
DOI: 10.1038/micronano.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable magnesium/iron batteries with polycaprolactone encapsulation: A microfabricated power source for transient implantable devices

Abstract: This study presents the design, fabrication, and testing of biodegradable magnesium/iron batteries featuring polycaprolactone (PCL) as a packaging and functional material. The use of PCL encapsulation minimized the electrochemical cell volume and supported longer discharge lifetimes and higher discharge rates than state-of-the-art biodegradable batteries. Specifically, the electrodes were separated and insulated by a 5 µm-thick PCL layer that served as both a battery packaging material and a permeable coating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 34 publications
0
81
0
Order By: Relevance
“…Copyright 2014, John Wiley and Sons. b) Left: Photograph of the PCL‐encapsulated liquid‐harvesting battery . Middle: Representative photographs of battery degradation during immersion in PBS 1× at 37 °C.…”
Section: Bioresorbable Electrical Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2014, John Wiley and Sons. b) Left: Photograph of the PCL‐encapsulated liquid‐harvesting battery . Middle: Representative photographs of battery degradation during immersion in PBS 1× at 37 °C.…”
Section: Bioresorbable Electrical Devicesmentioning
confidence: 99%
“…Right: Battery discharge in different aqueous solutions under a constant current density of 230 µA cm −2 . Reproduced under the terms of the CC BY license . Copyright 2015, Springer Nature.…”
Section: Bioresorbable Electrical Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…d) A miniaturized biodegradable Mg–Fe galvanic cell. Reproduced with permission . Copyright 2015, Springer Nature.…”
Section: Energy Storage Systemsmentioning
confidence: 99%
“…9 Recently, Nadeau et al demonstrated an ingestible battery based on Zn and Cu that is activated by gastric fluid. 10 Aside from the implantable applications, a biodegradable super capacitor was recently reported as an environmentally friendly energy storage solution.…”
mentioning
confidence: 99%